Study on Water Quality of Groundwater Supplies of Selected Location in Selangor: Serendah, Meru and Saujana Rawang - Krshnasri Murugan,; Saiful Rusman, Danish Irfan; Ngadiman, Norhayati (Multidisciplinary Applied Research and Innovation, 2024)
Groundwater utilisation is mostly common in some urban and rural area mostly in Kelantan, Terengganu, Selangor, Malacca. Many citizen in this particular area continue to employ the antiquated method of digging a well at home to collect water, despite the risks involved in using water that has not been treated.. A small locality in Selangor is one of the many villages that use this  practice. This study’s primary objective is to investigate the physical and chemical parameter of underground water in three different location in Selangor.The result of this study shows that the amount of Chemical Oxygen Demand (COD) and Ammonia Nitrogen (AN) is high in location M while Biochemical Oxygen Demand (BOD) is high in location SR. Location S is high in TSS whereas water hardness is high in location M and location SR.  As the conclusion, the underground use as supply water should undergo treatment before consumption need to follow Department of Environment (DOE)  underground water quality standard. Hence, it can be assure the safety and health of the water for the consumer.